The Dilemma of Ottoman Ex-Soldiers: Returning Home or Entering a New War - Murat Yolun (Yakın Dönem Türkiye Araştırmaları)
The armistice of Mudros, signed by the Ottoman Empire and the Allies, ironically brought about optimism and deep sadness among Ottomans. Soldiers and civilians wished that the Armistice would have heralded a peaceful period for the Empire that had experienced warfare since the Balkan Wars. However, the Ottoman soldiers had to choose whether to return to civilian life or resist the Allies’ occupation. Many veterans looked forward to restarting their civil lives, even though some high-ranking officers looked for ways to save their homes from invasion. The latter thought that the Allies were disrespectful to the articles in the armistice of Mudros or violated them. Thus, some of the Ottoman commanders postponed the demobilization of the army for the preparation of a post-war resistance. The self-narrated documents of soldiers’, especially the ones belonging to low-ranking soldiers, proved their reluctance for a new war due to their physical and psychological exhaustion. After all, many veterans desired to continue their lives as if nothing had happened in the Empire.